Dual-detector X-ray fluorescence imaging of ancient artifacts with surface relief - Smilgies, Detlef-M. (International Union of Crystallography, 2012)
Interpretation of X-ray fluorescence images of archeological artifacts is complicated by the presence of surface relief and roughness. Using two symmetrically arranged fluorescence detectors in a back-reflection geometry, the proper X-ray fluorescence yield can be distinguished from intensity variations caused by surface topography. This technique has been applied to the study of Roman inscriptions on marble.